Writing with new hands - Brandner, Walter (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
To analyse and compare the handwriting of a person under different circumstances — with origin hands, with a mechanical prosthesis and with new transplanted hands — it is necessary to have some information about the physical conditions. The handwriting of Theo Kelz proves that the writing is controlled by the brain. This leads to the conclusion that also under very difficult situations a forensic comparison of handwritings is possible.
Keywords: pismo ręczne z protezą; pismo z przeszczepionymi rękami